Towards a taxonomy of linguistic jokes - Lew, Robert (Adam Mickiewicz University, 1997)
A classification system for linguistic jokes is proposed: (1) verbal, (2) syntactic, (3) phonological, (4) orthographic, (5) deicitc reference, (6) specific vs nonspecific interpretation, (7) pragmatic ambiguity, (8) type of modality, & (9) multiple ambiguity. Under (3), it is noted that dialect differences can contribute to the relative success or failure of these jokes. In discussing (4), it is noted that this type may increase in popularity, due primarily to the pervasiveness of electronic communication & Internet access. Additionally, it is maintained that (4) should be considered a subtype, because other categories may also apply, making this a weaker taxonomic category.
Keywords: Linguistic humour; Linguistic humor; Humour; Humor; Jokes